Bioengineered nanomaterials - Tiwari, Atul; Tiwari, Ashutosh, 1978- (CRC Press, Taylor & Francis Group, 2014)
"This book focuses on the novel methodologies and strategies adopted during recent research and development of bioengineered nanomaterials for biomedical applications. It provides comprehensive and updated information on developments in this emerging area. The chapters discuss topics such as nanoemulsions as a vaccine adjuvant, bio-ceramic nanomaterials in medical applications, the potential of nanoparticles for the treatment of solid tumors and metastasis, natural and synthetic nanoporous membranes for cell encapsulation therapy, silver nanoparticles, nanotoxcity testing and bioapplications, inorganic nanoparticle materials for controlled release of drugs, and more"--Resumé vydavatele
Keywords: nanomedicína; nanočástice; bioinženýrství; biologické materiály; biomedicínské inženýrství; nanomedicine; nanoparticles; bioengineering; biological materials; biomedical engineering; sborníky; elektronické knihy; papers of several authors; electronic books